A Creative Nonfiction Narrative Inquiry into an EFL Online Learning Community During the COVID-19 Pandemic - Ypsilanti, Angeliki; Karras, Ioannis (GIST – Education and Learning Research Journal, 2022)
University libraries globally launch coronavirus memory archival projects inviting the documentation of personal experience. Elicitations such as journal entries and oral history interviews fall under the category of life-writing. This Narrative Inquiry focuses on creative nonfiction stories produced by an online high school community and edited by the EFL teacher during the first full lockdown in Greece. The shift to distance education caused students to use ELF as a means of contrasting their local archival endeavors with global ones. The EFL teacher as researcher used mentor texts, collected the coronavirus stories on e-me online platform, engaged the online members in a peer-reviewing process and reauthored a collective narrative. Narrative writing analysis was employed to reflect the teacher’s initiative to commemorate a student community’s physical disconnectedness from onsite learning. The use of e-me for this collaborative venture offers practical implications for EFL practitioners such as going beyond the bounds of the traditional curriculum whilst identifying self-regulation as indication of resilience among students experiencing unprecedented circumstances.